2018
DOI: 10.3846/ijspm.2018.440
|View full text |Cite
|
Sign up to set email alerts
|

Random Walks and Market Efficiency: Evidence From Real Estate Investment Trusts (Reit) Subsectors

Abstract: This paper investigates the random walk behavior of real estate investment trust (REIT) subsectors using monthly return data from January 1994 to July 2015. Using variance ratio tests, we examine subsectors of lodging/resorts and self-storage and find that they do not follow a random walk, contradicting the weak-form efficient market hypothesis. Non-parametric runs tests help us find that office, industrial, mixed, free standing, shopping centers, apartments, manufactured homes, and timberland subsectors are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…According to her, all methods show that, if any, diversification over types of property is a better strategy on the Swedish market than diversification across regions. Almudhaf and Hansz (2018) calculated the Sharpe ratio statistics for buy-and-hold and trading strategy portfolios of REIT subsectors for the sample period from January 1994 to July 2015 and found that some trading strategies' Sharpe ratios were larger than that of the buy and hold strategy. Almudhaf et al (2020) investigated the degree of return predictability of lodging/resort REITs for the period January 1994 to May 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to her, all methods show that, if any, diversification over types of property is a better strategy on the Swedish market than diversification across regions. Almudhaf and Hansz (2018) calculated the Sharpe ratio statistics for buy-and-hold and trading strategy portfolios of REIT subsectors for the sample period from January 1994 to July 2015 and found that some trading strategies' Sharpe ratios were larger than that of the buy and hold strategy. Almudhaf et al (2020) investigated the degree of return predictability of lodging/resort REITs for the period January 1994 to May 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a different level of risk of return on investment from individual buildings according to the method of their use. This is one of the consequences of the inhomogeneity of the real estate market [12]. Another determinant of the value of buildings is also the length of their service life which is already taken into account during their construction.…”
Section: Literary Researchmentioning
confidence: 99%